Effects of Physiotherapeutic Interventions on Quality of Life and Respiratory Function of subjects with COPD - Moura, Danilo de Macêdo; Moura, Suenny Marrocos de Lima; Gonçalves, Alessandra Feitosa; Silva, Maria Alessandra Sipriano da; Winkeler, Georgia Freire Paiva; Maciel, Simone dos Santos; Martins, Clarice Maria de Lucena; Santos, Heleodório Honorato dos (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Chronic Obstructive Pulmonary Disease (COPD) treatment includes a multidisciplinary approach, with physiotherapy a prominent role that promotes a positive impact on the quality of life (QOL) of these patients. Objective: To analyze the effects of physiotherapeutic interventions on QOL, lung volumes and capacities, and respiratory muscle strength in COPD patients. Methods: 17 subjects participated in the study, randomly divided into 2 groups: 1) Maneuvers: 62.7 ± 15.4 years, 1.65 ± 0.12 m, 81.4 ± 18.2 kg, body Mass Index (BMI) 29.9± 5.0 kg/m2 ; 2) Threshold: 64.4 ± 11.2 years, 1.58 ± 0.08 m, 70.7 ± 9.4 kg, BMI 28.6 ± 3.7 kg/m2 , with COPD, without neurological, musculoskeletal, cardiovascular or cognitive impairment, which made it impossible to participate in the physiotherapeutic intervention programs. QOL was analyzed using the Saint George Hospital questionnaire on Respiratory Disease (SGRQ); spirometry and respiratory muscle strength were analyzed by manovacuometry using a pneumotachograph. Data were analyzed in SPSS (20.0), Student’s t-test (paired) and Wilcoxon test were used for pre and post-intervention comparison of the SGRQ domains and total score, Vital Capacity (VC), Forced Vital Capacity (FVC), Forced Expiratory Volume (FEV1 ), Maximal Inspiratory Pressure (MIP) and Maximal Expiratory Pressure (MEP); and Student’s t-tests (independent) and Mann-Whitney were used in the intergroup comparison, all with a significance level of 5%. Results: There was a significant difference in both groups (P<0.05) in the pre- and post-intervention comparison of the three domains (Symptoms, Activities and Psychosocial Impact) and total SGRQ score, but this did not occur with spirometric variables. In the manovacuometry, the Wilcoxon test showed a significant difference in the pre and post-intervention values of MIP and MEP. Conclusion: Improved QOL and MIP and MEP muscle strength of all COPD patients was observed, regardless of the groups Maneuvers or Threshold.